Open Repair of a Young Hip Abductor Tendon Tears: A Case Report and Literature Review - Feng, Yao; Niu, Jing; Cui, Yujie; Jiang, Jun; Lu, Jike (Archives of Clinical and Medical Case Reports, 2025)
Greater trochanteric (GT) pain syndrome is a common debilitating hip condition featured by chronic lateral hip pain. This condition includes trochanteric bursitis, hip abductor pathology involving the gluteus medius and minimus, external coxa saltans (snapping hip syndrome), or combinations of those. Hip abductor tendon tears have been recognized as a main pain generator of the hip joints. This pathology is often misdiagnosed and left untreated because of the frequency of partialthickness undersurface tears. Once definite diagnosis is confirmed, nonoperative treatments are considered as the first therapeutic approach. Despite the availability and effectiveness of multiple non-operative therapies, a considerable percentage of patients will present with chronic disabling pain and refractory symptoms. Generally, most of general medical practitioners are unaware of accessible surgical approaches that benefit patients who are unresponsive to non-surgical managements. We report a case of 39-year-old female patient with chronic lateral hip pain refractory to conservative treatment for more than a year, then treated successfully with open abductor tendon repair. The patient returned to the desired activities six months following surgery without any reported complications. Follow up at a year and 2.5 years postoperatively, she has a pain free hip and normal functions of affected hip joint. In short, we reported an open surgical repair of the hip abductor tendons in the setting of a chronic full-thickness abductor tendon tear in a female patient after failure of nonsurgical managements. Preoperative accurate diagnosis is the key for successful reparation of the torn abductors.